Rock the Canal! A history of cultural life in the canal area of Brussels - Yves Rouyet (Brussels Studies)
Since the end of the 1970s, the canal area in Brussels has been an innovative setting for avant-gardist artistic creation in the area of non-traditional music, contemporary dance, theatre research and multidisciplinary and digital performances. Cultural operators have found affordable real estate there due to deindustrialisation and late and relatively slow residential gentrification. This article is aimed at identifying the key stages in the development of alternative culture in the canal area, within and especially outside recognised and subsidised institutions. It is based on the hypothesis that the artists and this unique area have had a mutual influence on each other. On the one hand, the area has enhanced artistic creation with its strong characteristics: urbanity, deindustrialisation and cosmopolitanism. On the other hand, the presence of cultural activities has attracted a public which has rarely been there, thus participating in the partial reconstruction of its image.